1927
DOI: 10.1084/jem.46.3.443
|View full text |Cite
|
Sign up to set email alerts
|

The Systolic Blood Pressure of the Normal Rabbit Measured by a Slightly Modified Van Leersum Method

Abstract: The blood pressure and pulse rate of 90 normal rabbits have been studied for various periods of time, from 1 day (accidental death interrupting the observation) to 15 months. The main data are presented in a table containing the blood pressure and pulse rate on the 1st day of observation, the maximum and minimum of both during the entire period of observation of each animal, together with the sex and weight of the animal. Separate tables are given showing the distribution of blood pressure, pulse rate and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1934
1934
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The pilot study using one rabbit and one rat also confirmed these findings and obligated us to use the rabbit model. Because the range of systolic blood pressure of the normal rabbit (70-170 mm Hg) (12) is similar to that of humans, in the experiment we used 12 mm Hg IAP. Furthermore, an intra-abdominal pressure of 12 mm Hg for the rabbit model was selected to approximate the laparoscopy pressures commonly used in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The pilot study using one rabbit and one rat also confirmed these findings and obligated us to use the rabbit model. Because the range of systolic blood pressure of the normal rabbit (70-170 mm Hg) (12) is similar to that of humans, in the experiment we used 12 mm Hg IAP. Furthermore, an intra-abdominal pressure of 12 mm Hg for the rabbit model was selected to approximate the laparoscopy pressures commonly used in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Holzapfel et al [8] did not consider a dependence of W on the second invariant of strain tr(C −1 ), so here we take C of the shear modulus for the artery's elastin matrix. We perform the stability analysis over a physiological pressure range [5] of 0-170 mmHg. We plot the results in Fig.7(c) for the non-dimensional measure of pressureP = P/C (s) 1 .…”
Section: Results For Soft Tissuesmentioning
confidence: 99%
“…However, other studies found no changes in blood pressure in humans after the administration of this drug [ 10 12 ]. Despite the significant decrease in MAP at moments M1 and M5, the treated animals showed no hypotension, given that the normal blood pressure of this species ranges from 70 mmHg to 170 mmHg [ 13 ].…”
Section: Discussionmentioning
confidence: 99%